Rowan Williams as Anglican Hegelian - Hobson, Theo (Reviews in religion and theology, 2005)
Books reviewed: Anglican Identities, Rowan Williams, Darton, Longman and Todd 2004 (0-232-52527-7), pp. viii + 149, Pb £7.95